Active management of suspected fetal macrosomia: the right approach? - Inmaculada Mejía; Patricia Barbero Casado; Claudia Sánchez-Arevalo; Christian Garrido Lopez; Laura Escudero Villegas; Antonio García Burguillo; Alberto Galindo; Cecilia Villalaín (The Journal of Maternal-Fetal & Neonatal Medicine)
Objective First, to analyze the impact on induction of labor, cesarean section and shoulder dystocia (ShD) rates after the application of an active management protocol in suspected isolated fetal macrosomia. Second, to determine the diagnostic yield of the third trimester scan for the prediction of neonatal macrosomia. Third, to compare baseline characteristics and perinatal outcomes in women with neonates ≥4000 g with and without prenatal suspicion of macrosomia.Methods A retrospective cohort study was conducted between July 2021 and July 2022 in a tertiary center. An active management protocol in suspected fetal macrosomia (estimated fetal weight (EFW) ≥97 custom percentile) after the third-trimester routine scan (between 34 + 0/35 + 6 weeks) in non-complicated pregnancies was applied. A 100-g oral glucose tolerance test (OGTT) was performed to rule out late-onset diabetes and a follow-up scan at 38–39 weeks scheduled. If the EFW was ≥4000 g in this second scan, labor induction within 2–4 days was offered. Maternal and perinatal outcomes were compared in macrosomic newborns (≥4000 g) according to prenatal suspicion of macrosomia.Results A total of 3543 deliveries were registered during the study period. 2832/3543 (79.9%) underwent their third-trimester routine scan, and in 197/2832 (6.9%) fetal macrosomia was suspected. In 147/197 (74.6%) OGTT was performed: 125/147 (85%) were normal and 22/147 (15%) were altered and excluded from further analysis. Among non-diabetic patients 125/125 (100%) had their follow-up scan of which 45/125 (36%) fetuses had an EFW ≥4000 g and 32/45 (71.1%) patients opted for an elective labor induction due to suspected fetal macrosomia (the rest did not meet induction criteria or initiated spontaneous onset of labor). The average neonatal weight in this group was 3975 ± 285 g. The mode of delivery was vaginal birth in 51.1% (23/45) and c-section in 48.9% (22/45). There were four cases of ShD among the 45 vaginal deliveries (8.9%). No perineal tears were diagnosed. Neonatal macrosomia after attempted vaginal birth was identified in 149 cases during the study period, of which 47/149 (31.5%) were antenatally suspected. When comparing the baseline characteristics and outcomes of prenatally suspected vs. unsuspected macrosomic newborns, differences were found in pregestational maternal body mass index (26.9 ± 5.7 vs. 25.9 ± 4.6, p = .03), maternal weight gain (kg) (12.8 ± 4.9 vs. 11.3 ± 4.8, p = .04), neonatal weight (g) (4198 ± 186 vs. 4177 ± 136, p = .04) and need of labor induction (68.1% vs. 44.1%, p = .04) but no differences were found in mode of delivery, ShD or perineal tear rates.Conclusions Third-trimester scan offers low detection rates of neonatal macrosomia. Prenatal macrosomia suspicion during the third trimester followed by active management did not improve perinatal results in this study when compared to non-suspected neonatal macrosomia.